P2X7 receptor/NLRP3 inflammasome complex and α‐synuclein in peripheral blood mononuclear cells: a prospective study in neo‐diagnosed, treatment‐naïve Parkinson’s disease - Solini, Anna; Rossi, Chiara; Santini, Eleonora; Giuntini, Martina; Raggi, Francesco; Parolini, Federico; Biancalana, Edoardo; Del Prete, Eleonora; Bonuccelli, Ubaldo; Ceravolo, Roberto (European journal of neurology, 2021)
Background and purpose Neuroinflammation and probably systemic inflammation, with abnormal α‐synuclein deposition, participate in the development of Parkinson's disease (PD). The P2X7 receptor/NLRP3 inflammasome complex is upregulated in the brain of PD patients. By a prospective approach, the degree of systemic activation of such complex, and its regulatory mechanisms, were explored in treatment‐naïve PD individuals. Methods The expression and functional activity of the inflammasome were measured in peripheral blood mononuclear cells of 25 newly diagnosed PD patients and 25 controls at baseline and after 12 months of pharmacological treatment, exploring the intracellular signalling involved and its epigenetic regulation. Results De novo PD patients were characterized by a systemic hyper‐expression of the P2X7R/NLRP3 inflammasome platform, probably able to modulate lymphomonocyte α‐synuclein, whose brain deposits represent the main pathogenetic factor of PD. A reduced c‐Jun N‐terminal kinase (JNK) phosphorylation might be the intracellular signalling mediating this effect. miR‐7 and miR‐30, implied in the pathogenesis of PD and in the post‐transcriptional control of α‐synuclein and NLRP3 expression, were also increased in PD. After 1 year of usual anti‐Parkinson treatments, such inflammatory platform was significantly reduced. Conclusions Mononuclear cells of newly diagnosed PD subjects display a hyper‐expression of the P2X7R/NLRP3 inflammasome platform that seems to modulate cellular α‐synuclein content and is reduced after PD treatment; an impaired JNK phosphorylation might be the intracellular signalling mediating this effect, undergoing an epigenetic regulation by miR‐7 and miR‐30. This study, performed in neo‐diagnosed Parkinson's disease patients, shows that a systemic hyper‐expression of the P2X7R/NLRP3 inflammasome platform is able to modulate circulating and lymphomonocyte α‐synuclein. This system is activated in an early phase of the disease, and undergoes a novel epigenetic regulation mediated by miRNAs showing a modulatory function in experimental models of the disease. A putative intracellular signalling responsible for this has also been identified. These results suggest a future use of the systemic evaluation of the P2X7R/NLRP3 complex in an integrated view of an early diagnosis and a correct identification of the main pathophysiological mechanisms of Parkinson's disease. ​